PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP MOTIVASI DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Putra, Gede Agus Eka; Subudi, Made (E-Jurnal Manajemen, 2017)
The purpose of this study was to analyze the effect of transformational leadership style and organizational culture on the motivation in improving organizational citizenship behavior in PT. BPD Bali Renon Branch. The population used in this study were all employees at PT. BPD Bali Branch Renon totaling 88 employees using census sampling techniques. The analysis technique used is the technique of path analysis. The analysis showed that transformational leadership and significant positive effect on the motivation of the beta coefficient 0,349. Organizational culture positive and significant impact on the motivation of the beta coefficient 0.352. Motivation positive and significant impact on organizational citizenship behavior with beta coefficient 0.393. Transformational leadership and significant positive effect on organizational citizenship behavior with beta coefficient 0.231. Organizational culture positive and significant impact on organizational citizenship behavior with a beta coefficient of 0.275.
Keywords: transformational leadership, organizational culture, motivation, organizational citizenship behavior